Genes of the mitochondrial apoptotic pathway in Mytilus galloprovincialis. - Noelia Estévez-Calvar (PLoS ONE, 2013)
Bivalves play vital roles in marine, brackish, freshwater and terrestrial habitats. In recent years, these ecosystems have become affected through anthropogenic activities. The ecological success of marine bivalves is based on the ability to modify their physiological functions in response to environmental changes. One of the most important mechanisms involved in adaptive responses to environmental and biological stresses is apoptosis, which has been scarcely studied in mollusks, although the final consequence of this process, DNA fragmentation, has been frequently used for pollution monitoring. Environmental stressors induce apoptosis in molluscan cells via an intrinsic pathway. Many of the proteins involved in vertebrate apoptosis have been recognized in model invertebrates; however, this process might not be universally conserved. Mytilus galloprovincialis is presented here as a new model to study the linkage between molecular mechanisms that mediate apoptosis and marine bivalve ecological adaptations. Therefore, it is strictly necessary to identify the key elements involved in bivalve apoptosis. In the present study, six mitochondrial apoptotic-related genes were characterized, and their gene expression profiles following UV irradiation were evaluated. This is the first step for the development of potential biomarkers to assess the biological responses of marine organisms to stress. The results confirmed that apoptosis and, more specifically, the expression of the genes involved in this process can be used to assess the biological responses of marine organisms to stress.